2016
DOI: 10.1080/00128775.2016.1201426
|View full text |Cite
|
Sign up to set email alerts
|

New Dimensions of Core-Periphery Relations in an Economically Integrated Europe: The Role of Global Value Chains

Abstract: This paper presents research conducted within the Competitiveness Research Network (CompNet). The network is composed of economists from the European System of Central Banks (ESCB) -i.e. the 28 national central banks of the European Union (EU) and the European Central Bank -a number of international organisations (World Bank, OECD, EU Commission) universities and think-tanks, as well as a number of non-European Central Banks (Argentina and Peru) and organisations (US International Trade Commission).The objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…The empirical findings of this study were compared with results available for the other European economies. Existing literature on economic internationalisation usually focuses on EU27 economies or the group of new member-states (Amador, Cappariello, & Stehrer, 2015;Grodzicki & Geodecki, 2016;Ederer & Reschenhofer, 2016;Breda, Cappariello, & Zizza, 2008), while the Croatian economy 1 is rarely included in the sample (Kersan-Skabi c, 2017). The results of this study provide additional evidence for the level of international integration of Croatia's economy and discuss the position of Croatia within the sample of selected NMS (new member-states) economies.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The empirical findings of this study were compared with results available for the other European economies. Existing literature on economic internationalisation usually focuses on EU27 economies or the group of new member-states (Amador, Cappariello, & Stehrer, 2015;Grodzicki & Geodecki, 2016;Ederer & Reschenhofer, 2016;Breda, Cappariello, & Zizza, 2008), while the Croatian economy 1 is rarely included in the sample (Kersan-Skabi c, 2017). The results of this study provide additional evidence for the level of international integration of Croatia's economy and discuss the position of Croatia within the sample of selected NMS (new member-states) economies.…”
Section: Introductionmentioning
confidence: 82%
“…Most studies conclude that a high share of import content is not generally perceived as a weakness, but rather as an indicator of the level at which domestic producers have achieved international integration in global value-added chains (Amador, Cappariello, & Stehrer, 2015;Grodzicki & Geodecki, 2016). However, improving the international competitiveness of domestic producers is the key prerequisite to ensuring an external stability in an environment of trade liberalisation and growing international integration (Ederer & Reschenhofer, 2016;Breda, Cappariello, & Zizza, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing literature is focused on the analysis of GVC participation or position. The EU as a whole, or selected EU members, are analysed, among others, by Amador, Cappariello and Stehrer (2015), Leitner and Stehrer (2014), Cieslik, Bieganska and Sroda-Murawska (2016), Grodzicki and Geodecki (2016), Timmer et al (2013), Timmer et al (2016). Amador, Cappariello and Stehrer (2015) found that in 2011 GVCs for the euroarea members (taken as a whole) were very important (as important as in China and more important than in the U.S. and Japan).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, they found the highest internationalisation in transport equipment and electronics where some of the countries were among the global leaders in the upstream segment. Grodzicki and Geodecki (2016) explain the core-periphery model in Europe based on the contribution of particular groups of countries to the value chain. They warn that GVC participation accelerates deindustrialisation processes and that the CEE countries are in a better position than the Southern countries, but this is due their continued dependence on foreign capital and technologies.…”
Section: Literature Reviewmentioning
confidence: 99%